The influence of nitrogen source and doping sequence on the electrocatalytic activity for oxygen reduction reaction of nitrogen doped carbon materials. (17th August 2016) - Zhan, Yunfeng; Yu, Xiang; Cao, Linmin; Zhang, Bodong; Wu, Xiaoxian; Xie, Fangyan; Zhang, Weihong; Chen, Jian; Xie, Weiguang; Mai, Wenjie; Meng, Hui
Abstract: The nitrogen doping effect on a kind of graphitic carbon as non noble metal catalyst for the oxygen reduction reaction is studied. Glycine and NH3 are chosen as different nitrogen source and different doping sequences are applied. The structural defect of graphitic carbon, total nitrogen content, types of nitrogen species and surface area are different from different treatment. Glycine will not influence the structure of graphitic carbon but NH3 introduces defects. Glycine introduces high content of nitrogen to graphitic carbon but NH3 introduces no nitrogen. The best catalyst is prepared by doping graphitic carbon with glycine first then heat treated with NH3 . Some of the nitrogen species can be removed by further NH3 treatment, but the relative content of graphitic nitrogen increases, together with increased surface area result in higher activity. Highlights: The nitrogen doping effect on a graphitic carbon is studied. Different nitrogen sources and different doping sequences are applied. The structural defect, nitrogen species and surface area determine ORR activity.